(untitled) (Eurasian Scientific Herald, 2024)
The development of students’ creative abilities in music lessons at school occurs organically, as they immerse themselves in the subject, as students’ artistic thinking is formed. Creativity is potentially inherent in all people and can be developed in all children to one degree or another. It is important to awaken the need for their development in time.